Marginalization of Women in Islam: Problem Interpretation - Ahmad Faisal (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2019)
This article aimed to find out the development of a view that tends to marginalize women is certainly not derived from religious teachings, but is more influenced by problems of interpretation. Although sourced from the same reference namely the Qur'an and Hadith, the interpretation of gender relations in Islam developed into diverse variants. Among the important factors that encourage diversity are the different perspectives on the inclusion of sociological and historical considerations in making interpretations. For interpreters who agree, historical elements, sociology must be taken into consideration in interpreting the verse. If the element is ignored, then the interpretation that appears will contain bias. That factor causes the interpretation paradigm of creation mythology, the involvement of women in the public sphere and several related issues about fiqh which seem contradictory to the main mission of Islamic teachings that puts forward the spirit of justice and equality. Therefore, reinterpretation of even the interpretation of interpretations is necessary. Therefore, it can easily reveal how far an interpretation correlates with the socio-cultural order of society when the interpretation is present. With this kind of paradigm, the discourse is distorted from the building of religious understanding which has been dominated by masculine interpretations, can be avoided.